Enhancing TREM2 expression activates microglia and modestly mitigates tau pathology and neurodegeneration - Kai Chen; Fuyao Li; Shuwen Zhang; Yixing Chen; Tadafumi C. Ikezu; Zonghua Li; Yuka A. Martens; Wenhui Qiao; Axel Meneses; Yiyang Zhu; Gisela Xhafkollari; Guojun Bu; et al. (Journal of Neuroinflammation)
Abstract TREM2, a microglia-specific receptor, is strongly associated with Alzheimer’s disease (AD) risk, mediating microglial responses to amyloid pathology critical to AD development. However, its role in tau pathology and neurodegeneration remains unclear. Using the PS19 tauopathy mouse model with inducible overexpression of human wild-type TREM2 (TREM2-WT) or the R47H variant (TREM2-R47H), we show that increasing TREM2-WT expression modestly reduces soluble phosphorylated tau levels and mildly preserves neuronal integrity. Single-cell RNA sequencing reveals that TREM2-WT robustly enhances microglial activation, characterized by a disease-associated microglia (DAM) signature. In contrast, TREM2-R47H overexpression exhibits a loss-of-function phenotype, with no significant impact on tau levels, neurodegeneration, or microglial activation. These findings highlight the role of TREM2 in modulating microglial activity and its influence on tau pathology and neurodegeneration, providing important insights for the future development of therapies targeting TREM2 or microglial pathways in AD or other tauopathies.